Extraction and Application of Natural Dye from Gladiolus on Cotton and Cotton/Polyester Blend: Extraction of dye from Gladiolus - Ijaz, Mehreen; Sahar, Namood-e- (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2020)
The current study aims at determining the role of natural dye on cotton and cotton/polyester blends. The research work was conducted at Nishat Mills Limited (Dyeing and Finishing Unit). The dye was extracted from the floral part of Gladiolus in three different shades and applied on selected fabrics. The dyed material was then tested for its light and colourfastness and visual assessment by following AATCC Test Method 8-2007 and AATCC Evaluation Procedure 9-2007 respectively. The results indicated that dyed samples showed excellent to moderate colourfastness in dry and wet conditions. Specimen A-1 comprised of 100% cotton showed excellent results with 5 grayscale readings for red colour. Darker shades were observed for the same red colour in specimen A-1 with selected four illuminants. Chroma was observed as brighter for all three shades when observed under cool white illuminant. The findings can be helpful for the dyeing units in textile industries for the adoption of natural and eco-friendly products and procedures.